Conservation conflicts involving mammals in Europe - Delibes-Mateos, Miguel (THERYA, 2014)
Introduction: In recent times, conflicts involving wildlife have increased in importance and magnitude. Conservation conflicts occur when two or more parties with strongly held opinions clash over conservation objectives, and when one party is perceived to assert its interest at the expense of another. Conservation conflicts usually emerge from â€œwildlife impactsâ€, defined as circumstances where people, consciously or unconsciously, negatively impact wildlife, or alternatively where wildlife negatively impacts the well-being or livelihoods of people or biodiversity. In Europe, the most frequent and intense conservation conflict associated with the management of mammals is likely that involving predators. For example, large carnivores depredate on livestock and game species, but at the same time these are flagship-species for European nature conservation. Therefore, conflicts about how these species should be managed emerge frequently. The management of overabundant ungulates that negatively impact natural vegetation as well as that of small mammals that damage crops also lead to frequent clashes between stakeholders in Europe. The global conservation status of most conflictive European mammals is rather good. However, some of their populations are threatened, at least partially by illegal killing and poaching. From this perspective, efforts are needed to mitigate conservation conflicts in these areas. In addition, promoting the investigation of conservation conflicts that incorporates multidisciplinary approaches is essential to increase the understanding of such conflicts and ultimately to mitigate them. Key words: Crop damage, hunting, large carnivores, livestock loss, overabundant ungulates, poaching, predator control, small mammals, wildlife management